Digital Transformation Mediation on Entrepreneurial Leadership, Innovation Management, Social Capital Impacts MSME Performance - Selfiana Selfiana; Akka Latifah Jusdienar; Widya Nengsih; Harries Madiistriyatno; Ratnawita Ratnawita (Annals of Human Resource Management Research, 2026)
Purpose: The purpose of this research is to examine the impact of entrepreneurial leadership, innovation management, and social capital on MSME performance: with digital transformation mediation in east java. Research Methodology: A quantitative approach was employed involving 130 MSME owners. Data analysis and hypothesis testing were conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) path analysis and the bootstrapping technique to examine the relationships among the key variables in the study. Results: The findings show that Entrepreneurial Leadership and Social Capital are important drivers of digital transformation among MSMEs in East Java. Innovation Management becomes more effective through digital technology mediation. However, limited digital infrastructure and low digital literacy remain challenges. Therefore, strengthening digital capabilities, supportive policies, and social capital is essential for MSME growth. Conclusions: Digital transformation improves MSME performance by expanding market access and increasing their operational efficiency. Entrepreneurial leadership, social capital, innovation management, and policy support are essential for strengthening sustainable MSME growth in East Java. Limitations: This study only examines the independent variables, namely entrepreneurial leadership, innovation management, and social networks, even though there are many other independent variables that can influence MSMEs. Contributions: This type of research contributes to understanding how to enhance MSME competitiveness by examining how these core elements, combined with digital adoption, drive growth and success Novelty: This study is novel in that it develops an integrative model that places digital transformation as a strategic mediating variable in the relationship between entrepreneurial leadership, social capital, and innovation management on the sustainability of MSMEs, especially in the context of developing regions with limited infrastructure and digital literacy.